Exploring Pedagogical Representation of Visual Images in EFL Textbooks: English in Focus for Grade VII Junior High School - Ine Suminar; Vanessa Dwi Septianti; Cindy Febrianthy (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2025)
This study aims to explore the pedagogic visual images used in the English in Focus textbook for Grade VII junior high school students and to assist teachers in critically evaluating the textbooks they utilize. The primary goal is to examine how visual images are incorporated into English as a Foreign Language (EFL) textbooks to support systematic knowledge acquisition, enhance learner motivation, and facilitate engagement and language proficiency development. The research employs a descriptive qualitative method, analyzing selected visual and verbal elements in the textbook. The instruments used include a checklist for verbal analysis based on Eggins (2004) and a framework for visual analysis derived from Van Leeuwen (2006). The data consist of 80 images, analyzed to identify representations of ideational, interpersonal, and textual metafunctions. The findings show that the textbook effectively combines verbal and visual modes. Verbal elements emphasize relational processes to deliver clear information, declarative statements for interaction, and multiple themes for varied ideas. Visual elements rely on narrative processes, indirect gaze, long-shot perspectives, and left-right information distribution for coherence. These results underline the importance of visual literacy in EFL classes and well-designed textbooks. The English in Focus textbook meets its objectives with an organized layout and clear content, promoting learner engagement and enabling consistent evaluation across grades.